Clinoptilolite-based mixed matrix membranes for the selective recovery of potassium and ammonium. (1st March 2016) - Casadellà, A.; Kuntke, P.; Schaetzle, O.; Loos, K.
Abstract: A clinoptilolite-based mixed matrix membrane (MMM) was developed and studied for the selective recovery of ammonium and potassium. Adsorption of sodium (Na + ), potassium (K + ) and ammonium ( NH 4 + ) was investigated with single salt and equimolar salt solution under static and dynamic conditions. Furthermore, the adsorption capacity of clinoptilolite was investigated when embedded in the MMM and in clay form. Two conditioning methods were compared: HCl and NaCl. Conditioned clinoptilolite with NaCl gave higher static adsorption capacities than with HCl which alters the chemical structure of clinoptilolite. The adsorption of Na + was not detected in the static adsorption experiments and results showed that Na + adsorbed during the conditioning process it was exchanged by K + and NH 4 + .The clinoptilolite embedded in MMM reduced the porosity of the MMM so the highest adsorption capacity was reached when the amount of polymer was the lowest: 30 wt% polymer and 70 wt% clinoptilolite. The application of MMM in a dead-end filtration cell (dynamic adsorption) resulted in higher adsorption capacities compared to static conditions and comparable results between synthetic solutions and diluted urine samples. This indicates that MMM is a suitable method for the recovery of K + and NH 4 + directly from a diluted urine matrix. The desorption (recovery) of K + and NH 4 + from MMM was higher using water at 60 °C than using an acidic treatment. Graphical abstract: Highlights: We studied the adsorption capacity of clinoptilolite in clay for K +, NH 4 + and its capacity to separate Na + . We developed clinoptilolite-based mixed matrix membranes (MMMs) and studied their adsorption capacity. MMM presented a lower adsorption capacity than clay although the relative removal efficiencies (RK, NH4 ) remained comparable. Dynamic adsorption tests gave similar results for synthetic solutions than for fresh urine. Ultrapure water at 60 °C gave better desorption properties than acidic conditions (1.0 M HCl) at 25 °C.